2007
DOI: 10.1152/ajpcell.00161.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β increases expression and activity of matrix metalloproteinase-2 in cardiac microvascular endothelial cells: role of PKCα/β1 and MAPKs

Abstract: Mountain DJ, Singh M, Menon B, Singh K. Interleukin-1␤ increases expression and activity of matrix metalloproteinase-2 in cardiac microvascular endothelial cells: role of PKC␣/␤ 1 and MAPKs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 59 publications
6
66
1
4
Order By: Relevance
“…We reported previously that basement membrane degrading enzyme, matrix metalloproteinase-2 (MMP-2), is downregulated by shear stress in a p38 dependent manner (Milkiewicz et al, 2006). Conversely, ERK1/2 activation increases MMP-2 production (Boyd et al, 2005;Mountain et al, 2007). ERK1/2 also promotes proliferation in endothelial cells (Pages et al, 2000;Pages et al, 1993), and minimal proliferation occurs during shear stress-mediated angiogenesis (Zhou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously that basement membrane degrading enzyme, matrix metalloproteinase-2 (MMP-2), is downregulated by shear stress in a p38 dependent manner (Milkiewicz et al, 2006). Conversely, ERK1/2 activation increases MMP-2 production (Boyd et al, 2005;Mountain et al, 2007). ERK1/2 also promotes proliferation in endothelial cells (Pages et al, 2000;Pages et al, 1993), and minimal proliferation occurs during shear stress-mediated angiogenesis (Zhou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of myocardial infarction (MI) closely depends on a adequate ventricular architecture remodeling. The process is mainly driven by the deposition of ECM macromolecules in a tightly regulated manner in order to prevent stiffness and/or other pathological conditions that often impairs myocardial viscoelasticity ending up with a heart failure (Mountain et al, 2007). The role of MMP-2 in cardiac tissue encompasses critical steps in heart and cardiovascular system development during embryogenesis: nonetheless, the enzyme is well represented in pathological conditions that require ECM remodeling and restoration of cardiomyocytes homeostasis (Linask et al, 2005).…”
Section: Biological Aspectsmentioning
confidence: 99%
“…All the activated MMPs (including MMP2 and MMP9) are specifically inhibited by endogenous inhibitors, tissue inhibitor of metalloproteinases (TIMPs; Visse & Nagase 2003, Kessenbrock et al 2010). MMP2 and MMP9 can be induced in multiple cells by inflammatory cytokines including interleukin 1b (IL1b (IL1B)) and tumor necrosis factor a (TNFa; Mackay et al 1992, Li et al 1999, Siwik et al 2000, Jones et al 2005, Redondo-Munoz et al 2006, Mountain et al 2007. Our pervious study showed that IL1b increased the permeability of the human umbilical vein endothelial cell (HUVEC) monolayer by damaging adherens junctions and enlarging the junctions cleft width (Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%